Atrial fibrillation in patients undergoing coronary artery surgery is associated with adverse outcome. (2nd January 2019) - Batra, Gorav; Ahlsson, Anders; Lindahl, Bertil; Lindhagen, Lars; Wickbom, Anders; Oldgren, Jonas
Abstract: Background: The aim was to determine the association between atrial fibrillation (AF) and outcome in patients undergoing coronary artery bypass grafting (CABG). Methods: All patients undergoing CABG between January 2010 and June 2013 were identified in the Swedish Heart Surgery Registry. Outcomes studied were all-cause mortality, cardiovascular mortality, myocardial infarction, congestive heart failure, ischemic stroke, and recurrent AF. Patients with history of AF prior to surgery (preoperative AF) and patients without history of AF but with AF episodes post-surgery (postoperative AF) were compared to patients with no AF using adjusted Cox regression models. Results: Among 9, 107 identified patients, 8.1% ( n  = 737) had preoperative AF, and 25.1% ( n  = 2, 290) had postoperative AF. Median follow-up was 2.2 years. Compared to no AF, preoperative AF was associated with higher risk of all-cause mortality, adjusted hazard ratio with 95% confidence interval (HR) 1.76 (1.33–2.33); cardiovascular mortality, HR 2.43 (1.68–3.50); and congestive heart failure, HR 2.21 (1.72–2.84). Postoperative AF was associated with risk of all-cause mortality, HR 1.27 (1.01–1.60); cardiovascular mortality, HR 1.52 (1.10–2.11); congestive heart failure, HR 1.47 (1.18–1.83); and recurrent AF, HR 4.38 (2.46–7.78). No significant association was observed between pre- or postoperative AF and risk for myocardial infarction and ischemic stroke. Conclusions: Approximately 1 in 3 patients undergoing CABG had pre- or postoperative AF. Patients with pre- or postoperative AF were at higher risk of all-cause mortality, cardiovascular mortality, and congestive heart failure, but not of myocardial infarction or ischemic stroke. Postoperative AF was associated with higher risk of recurrent AF.